Impact of Quantitative Easing Policy on Labor Market: The Case of The United States and The Euro Area Between 2000 And 2019 - Maciej BOLISEGA (Communications of International Proceedings, 2021)
The aim of conducted research was to analyze the impact unconventional monetary policy on labor market. A vector autoregression (VAR) was applied in order to estimate impulse response function of unemployment rate in analyzed economies. The results provide evidence that unconventional monetary policy conducted between 2000 and 2019 by the Federal Reserve System in United States was more effective, considering the impact on labor market, than the policy conducted by European Central Bank in the euro area in the same period.
Keywords: Monetary policy; quantitative easing; European Central Bank; federal reserve system